A referenciação catafórica: uma proposta de categorização e análise - Fernandes, Maria José da Silva (2010)
The study presents a research on one cohesion mechanism - the cataphoric referenciation - that refers ahead to one text referent. That is to say that an entity is evoked before its presentation on the text. The aim of the study is to categorize cataphora types and their textual referents as we identify the linguistic elements used cataphorically and the textual referents functions. We analyzed, in the corpus, cataphoric occurrences of personal, demonstrative and indefinite pronouns; adverbs; numbers; and nominal expressions. The cataphoric references found were classified as pronominal, nominal and associative. The former has a pronoun, a number or an adverb as its remissive form and it has an explicit textual referent. The second presents a nominal expression as its remissive form, and has an explicit textual referent. The latter is named associative because it does not have an explicit textual referent, as the referent must be inferred by the reader from co-textual and contextual clues. According to the corpus, this cataphora type is a pronoun. The textual referents were categorized as common nouns, proper nouns, nominal expressions, simple and compound sentences and whole texts. The functions of the textual referents were also analyzed. The theoretical basis is Text Linguistics, mainly the studies about referenciation (MONDADA & DUBOIS, 2003), negotiation process within discourse. The corpus is 193 journalist newspaper articles from Folha de São Paulo and Veja magazine, published in the second semester of 2008. We found a major occurrence of pronominal cataphora (55%), followed by the nominal (41,15%), and the associative (3,85%). The most used category of pronominal cataphora are personal pronouns, the indefinite pronouns were most used as associative cataphora. The most common pattern of nominal cataphora is determiner + noun + modifier. The cataphora occurs more frequently within the text. The most common textual referents functions are to specify, to explain and to enlighten. According to the results, we can claim that cataphora use as referential mechanism has been frequently used in journalistic context. It helps the organization, the progression, and the focus on some segments from the text. Finally, we can state that cataphora can be used as a way of catching the reader´s attention.